The Effect of Ratio of Chayote with Pineapple and Addition of Sugar on Quality of Jam - Dapot Parulian Sitio; Sentosa Ginting; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of the research was conducted to determine the effect of ratio of chayote with pineapple and addition of sugar on quality of  jam. This research was using a factorial completely randomized design with two factors: ratio of chayote with pineapple (N) : 90%:10%, 80%:20%, 70%:30%, 60%:40%, and sugar (G): 35%, 45%, 55%, 65%. Parameters observed were water content, ash content, vitamin C content, total acid, pH, total soluble solid, sensory test of color, flavor, taste and value skor of spreadness.The results showed that the ratio of chayote with pineapple had highly significant effect on all parameters except value of spreadness.. Sugar had highly significant effect on all parameters. Interaction between ratio of chayote with pineapple and sugar had highly significant effect on ash content and sensory test flavor, had no significant effect on water content, vitamin C content, total acid, pH, total soluble solid, sensory  test color, taste and value of spreadness. The ratio of chayote with pineapple of 60%:40% and sugar of 65% produced the best chayote jam. Keyword: chayote, jam, pineapple, sugar